Analysis of the Areas of Integration between Policies and Regulatory Procedures under ISA 315 and Governance Mechanisms: An Analytical Study from the Perspective of External Auditors in Baghdad - Sabih Alsaffar , Sohad; Noor Sabah Hussein, Noor Sabah Hussein (Journal of Economics and Administrative Sciences, 2025)
The study aims to design a methodology that directs attention to areas of weakness in the control policies, procedures, and mechanisms that should be taken into account when implementing audit tasks and determining the size, nature, and extent of designing substantive tests as part of the auditor's tasks. The significance of the research is based on the following hypotheses: The first is "The auditor's assessment of control policies and procedures using an approach based on the integration of ISA315 with corporate governance mechanisms helps strengthen his opinion about the effectiveness of those policies and procedures." The researchers prepared the applied aspect of examining and analysing the policies and procedures of the international standard ISA315 and the requirements of the mechanisms through an examination form designed to collect information about activities related to governance, procedures, and instructions. The research outlines a set of conclusions, the most important of which are: Control policies and procedures based on ISA315 are effective from the auditor's perspective when they maintain the integration of information with the requirements of governance mechanisms. To achieve this, various controls must be available to examine the accuracy and completeness and delegate transaction powers. Additionally, there is a statistically significant relationship between the control policies and procedures based on ISA 315 and the governance mechanisms. Finally, a statistically significant relationship was found for the auditor’s responsibility to understand the control policies and procedures and work within the governance mechanisms.